Methods and Design of Cost and Cost-Effectiveness Study to Compare Different Modalities for Collecting Individual-Level 24-Hour Dietary Recalls in Burkina Faso and Viet Nam. (29th May 2020) - Coates, Jennifer; Rogers, Beatrice; Adams, Katherine; Bell, Winnie; Some, Jerome; Colaiezzi, Brooke; Wafa, Sarah; Prata, Cathleen
Abstract: Objectives: Collection of individual level dietary data in low and middle income countries traditionally has been hindered by complexity and high costs. To address this issue, the International Dietary Data Expansion (INDDEX) Project has developed an innovative dietary assessment platform (INDDEX24) consisting of a tablet-based application for conducting individual 24-hour dietary recalls (24HR), linked to a set of web-based dietary data inputs (e.g., food composition database, standard recipes, conversion factors). The objective of this study was to compare cost, time and cost effectiveness of a 24HR using INDDEX24 versus a standard pen-and-paper (PAPI) approach. Methods: Costs of implementing 24HR using INDDEX24 vs. PAPI were derived using activity-based costing methods as part of two validation studies conducted with adult women in Burkina Faso ( n = 231) and Viet Nam ( n = 234). To estimate the time of survey administration, we surveyed 60 respondents per country in urban and rural areas. Other costed activities included: developing dietary data inputs, survey preparation and implementation, data entry, processing, and analysis. Monetary and time costs were compared in total and for each activity. Cost effectiveness was defined as relative cost per unit of accuracy, with accuracy determined by the difference of INDDEX24 and PAPI compared to a weighed food record (WFR). Results: This study identified multiple challenges associated with assessing the cost side of a cost-effectiveness analysis. The overall cost, time, and cost-effectiveness can vary significantly by country, as well as by specific activities in each context. Another challenge was distinguishing costs related to the implementation of the INDDEX24 validation study from those that future users will face. Modeled scenarios distinguished the up-front costs of developing and validating the INDDEX24 platform from the expected implementation costs of using it. Conclusions: The selection of the most appropriate dietary assessment approach should be based on considerations of time, cost, and accuracy. This cost study, together with findings from the INDDEX24 validation study, shows the potential for INDDEX24 to streamline 24HR by saving time and resources. Funding Sources: Bill and Melinda Gates Foundation.